Macular Edema in Childhood Uveitis - Garweg, Justus G. (Klinische Monatsblätter für Augenheilkunde, 2018)
Background Pediatric uveitis is associated with a high incidence of severe and frequently permanent visual loss. This article summarizes the current understanding of the disease and the therapeutic options that are available to improve treatment outcomes.Methods A Medline search spanning the last 10 years was undertaken using the key terms “pediatric uveitis” or “childhood uveitis” and “macular edema”. Articles which appertained to case reports or small case series were excluded from consideration, whereas those in which the opinions of experts were expressed, as well as reviews, were not. The information contained in these latter two forms of publication was particularly valuable, owing to the scarcity of prospective clinical data appertaining to the treatment of pediatric uveitis-associated macular edema.Results Ten years ago, 34% of children who presented with uveitis manifested secondary complications at the time of diagnosis. During the ensuing 3 years of treatment, this rose to 86%. Heightening awareness of the disease with earlier referrals to expert centers, as well as the advent of therapeutic strategies involving anti-TNF agents and intravitreal corticosteroids, have led to a decrease in the incidence of legal blindness in the affected eyes from 18 – 69% to below 8% during a five-year course of treatment.Conclusion Early diagnosis and strict control of inflammatory activity have led to a dramatic reduction in the incidence of vision-threatening secondary complications. In the majority of cases, it has also been possible to resolve cystoid macular edema, which, if insufficiently controlled by systemic therapy, usually responds well to intravitreal dexamethasone implants.
Keywords: pediatric uveitis; macular edema; vision loss; complications; intraocular inflammations; pediatric ophthalmology